DNA twisting and the affinity of bacteriophage 434 operator for bacteriophage 434 repressor. - Koudelka, G B (1988)
The affinity of the Escherichia coli phage 434 operator for phage 434 repressor is affected by changes in the sequence of the noncontacted base pairs near the operator's center. The results presented here show that base composition near the center of the operator affects the operator's affinity for repressor by altering the ease with which the operator can be overtwisted into the proper configuration for complex formation. We show that both DNA flexibility and repressor flexibility influence the strength of the repressor-operator interaction: an operator with a single-strand nick at its center has a higher affinity for repressor than does the intact operator: and a repressor bearing a mutation that results in a relaxed dimer interaction is less sensitive than is wild type to changes in the flexibility of the operator. We show that the effect of noncontacted base pairs on operator affinity is independent of the slight overall bend of the operator seen in the repressor-operator complex. Central sequence effects on affinity for repressor are independent of the identity of adjacent base pairs, suggesting that the structure of the individual base pairs, not interactions between them, are responsible for the different torsional rigidities of different operators.